2013
DOI: 10.1371/journal.pone.0062986
|View full text |Cite
|
Sign up to set email alerts
|

The Metastasis-Associated Gene MTA3, a Component of the Mi-2/NuRD Transcriptional Repression Complex, Predicts Prognosis of Gastroesophageal Junction Adenocarcinoma

Abstract: Gastroesophageal junction (GEJ) adenocarcinoma carries a poor prognosis that is largely attributable to early and frequent metastasis. The acquisition of metastatic potential in cancer involves epithelial-to-mesenchymal transition (EMT). The metastasis-associated gene MTA3, a novel component of the Mi-2/NuRD transcriptional repression complex, was identified as master regulator of EMT through inhibition of Snail to increase E-cadherin expression in breast cancer. Here, we evaluated the expression pattern of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 32 publications
0
33
0
Order By: Relevance
“…12 In addition, MTA3 expression was an independent prognostic factor in patients with gastroesophageal junction adenocarcinoma. 13 To date, its clinical significance and biological characteristics in colorectal carcinoma have not been well investigated. In this study, we demonstrated MTA3 protein expression was higher in CRC tissues than that in normal colon tissues.…”
Section: Discussionmentioning
confidence: 99%
“…12 In addition, MTA3 expression was an independent prognostic factor in patients with gastroesophageal junction adenocarcinoma. 13 To date, its clinical significance and biological characteristics in colorectal carcinoma have not been well investigated. In this study, we demonstrated MTA3 protein expression was higher in CRC tissues than that in normal colon tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Functionally, sex steroid receptors such as estrogen receptor (ER) and androgen receptor (AR) serve as transcription factors by recruiting multiple coactivators . By collaborating with transcription factors, coactivators play crucial roles in chromatin remodeling and regulation of gene expression . Nuclear receptor coactivator 1 (NCOA1, also known as SRC‐1) is the founding member of the nuclear receptor coactivator family .…”
Section: Introductionmentioning
confidence: 99%
“…4,5 By collaborating with transcription factors, coactivators play crucial roles in chromatin remodeling and regulation of gene expression. [6][7][8][9][10][11][12] Nuclear receptor coactivator 1 (NCOA1, also known as SRC-1) is the founding member of the nuclear receptor coactivator family. 2,13 In addition to serving as a coactivator of AR 14,15 and ER, 16,17 NCOA1 is also involved in transcriptional regulation of genes by interacting with other transcriptional factors.…”
Section: Introductionmentioning
confidence: 99%
“…The MTA3 gene is a member of the metastasis‐associated protein family, identified as key regulators of the epithelial‐mesenchymal transition process and E‐cadherin expression . MTA3 has been described to be under‐expressed in some malignancies, including breast cancer, ovarian cancer, gastroesophageal junction adenocarcinoma or endometrial cancer, and even as a suppressor of metastases in these tumors . Shan et al described decreased MTA3 expression in glioma and its association with prognosis, which suggests that MTA3 is a suppressor gene in this malignancy.…”
Section: Discussionmentioning
confidence: 99%